Teaching Common English Language Expressions for Hotel Staff: Best Practices - Nurdiana, Nurdiana (English Journal Antartika, 2024)
The hospitality industry is closely linked to the English language, as proficiency in English is essential for effective communication within this field. However, many hotel staff members in Indonesia struggle to communicate in English appropriately, highlighting the need for improvement. To address this, regular training programs should be implemented to enhance language skills, focusing on practical English used in hospitality settings. This study aims to explore teaching common English expressions to hotel employees. Using a descriptive-qualitative approach and reviewing relevant studies, the findings suggest that certain language functions and expressions are frequently used in hospitality and should therefore be incorporated into the training programs for hotel staff.